An infant with testicular Fetus-in-fetu in the abdominal cavity: rare case report - Luo, Mingshuang; Li, Geng; Gao, Heyun; Zhang, Wen (Frontiers in Pediatrics, 2024)
Background: Fetus-in-fetu (FIF) represents an exceedingly rare disease, characterized as an encapsulated and pedunculated vertebrate neoplasm, typically lacking cerebral tissue. The prevalence shows no gender preference. Notably, FIF can cause compressive damage to adjacent organs and tissues, potentially impeding the host's development and maturation.Case Presentation: A four-month-old male infant was identified, during pregnancy, to have a left-sided pelvic mass on ultrasound. Subsequent evaluations suggested the mass could be a FIF, exhibiting active movement. Surgical exploration revealed that the mass's left boundary was connected to the left spermatic cord and vas deferens.Pathological analysis post-surgery showed the absence of testicular tissue, but the presence of skin tissue, cartilage-like structures, and gastrointestinal elements.Additionally, localized tissue resembling vertebrae confirmed the diagnosis of testicular FIF.An intraperitoneal testicular FIF is extremely rare, with its cause still unknown. This groundbreaking report details the diagnosis and management of such a case. Following a FIF diagnosis, prompt surgical removal is crucial, along with regular follow-up using ultrasound and tumor markers.